The Challenges of the Young Generation in Facing the Current of Hedonism with Strengthening the Values of Pancasila - Puspasari, Deyana (Journal of Creativity Student, 2018)
Character education to revitalize the resilience of the nation must be carried out immediately, because there are many multidimensional crises faced by the Indonesian people. The multi-dimensional crisis is caused by changes in the dynamics of the world order with the strengthening of globalization. They are also caused by modernization, industrialization, regional autonomy, environmental, moral and intellectual degradation, the potential for conflicts between groups (racial, ethnic, religious), as well as by the infrastructure of the nation, state, and society that are prone to crisis. Character education aims to optimize the load of goods with good and positive character (characteristics, attitudes, and behaviors of nobles who become strong grips and authorized individuals and development of the nation in the future. Education is considered a very important character both at various levels and opportunities, it also starts at home, school, to social life. Instilling the values and spirit implied in Pancasila and Bhinneka Tunggal Ika can be developed into a reality in strengthening national identity, which can be an inspiration for strengthening national character education. The future, especially in terms of national character education, must be shared by the two countries, the community, and all components of the Indonesian nation.